Acute effects of diclofenac on zebrafish: Indications of oxidative effects and damages at environmentally realistic levels of exposure - Bio, Sofia (2022)
With the increasing awareness about the contamination of the aquatic environment by pharmaceuticals, there is a growing need to study their adverse effects on aquatic organisms. Diclofenac is a non-steroidal anti-inflammatory drug (NSAID), whose wide use contributes for its presence in freshwater ecosystems, increasing the probability of causing deleterious changes in aquatic biota. This study evaluated possible oxidative stress effects in Danio rerio embryos and larvae when exposed to a range of ecologically relevant concentrations of diclofenac. It was possible to conclude that diclofenac caused a scenario of oxidative stress, since all tested toxicological parameters were responsive to the drug. In general, diclofenac caused not only significant anti-oxidant adaptive responses for most levels of exposure, but also peroxidative damage. This work evidenced the responsiveness of D. rerio towards diclofenac in environmentally relevant concentrations, which shows that these organisms might face a scenario of oxidative stress in their natural habitat.